1988
DOI: 10.1073/pnas.85.2.617
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deficiency of the alpha subunit of the guanine nucleotide-binding protein Gs as the molecular basis for Albright hereditary osteodystrophy.

Abstract: Patients who have pseudohypoparathyroidism type I associated with Albright hereditary osteodystrophy commonly have a genetic deficiency of the a subunit of the G protein that stimulates adenylyl cyclase (aG3) (ATP pyrophosphate-lyase, EC 4.6.1.1). To discover the molecular mechanism that causes aG5 deficiency in these patients, we examined eight kindreds with one or more members affected with Albright hereditary osteodystrophy or pseudohypoparathyroidism and aG. deficiency. In these families, aG. deficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…The GP antisera recognized a single 36-kD band in erythrocyte membranes (Fig. 1 C) (24)(25)(26). Levels of Gsa were increased in FHP subjects using two independent techniques, immunoblot analysis and cholera toxin-induced ADP-ribosylation.…”
Section: Resultsmentioning
confidence: 99%
“…The GP antisera recognized a single 36-kD band in erythrocyte membranes (Fig. 1 C) (24)(25)(26). Levels of Gsa were increased in FHP subjects using two independent techniques, immunoblot analysis and cholera toxin-induced ADP-ribosylation.…”
Section: Resultsmentioning
confidence: 99%
“…However,we have only found 4 patients to date, who showed symptoms within a year after blood transfusion among 53 patients in Kagoshima district; excluding the present patient, the other three showedinsidious onset after gastric cancer operation. The results indicated that this patient had had PPHP (4,5). In patients receiving blood transfusion, preexisting PHP la or PPHPis a risk for contracting HAM/TSP rather than HTLV-I causing PHP la or PPHP, as described previously (1, 2), although the quantity of infecting virus in the blood transfusion, the reason for surgery, and the postoperative condition were also factors.…”
Section: Pphrmentioning
confidence: 76%
“…The findings that urinary cAMP excretion in response to exogenous PTH is reduced or absent and of an excessive TSH response to TRH are consistent with inadequate activation of the PTH-and TRH-responsive adenylyl cyclase and different isotypes thereof, and activation of phosphodiesterase (4,16). To this end, G s activity was shown to be reduced (7)(8)(9)(10)(11). Subsequently, several mutations of the G s ␣-encoding gene have been discovered (12-16).…”
Section: Discussionmentioning
confidence: 97%